Therapeutic impact of Telomerase Inhibitor Imetelstat: A Literature Review - Mohamed Ziedan; Dina Salah; Maha Ayman (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
The immortal phenotype of cancer cells is a significant trait, and in the vast majority of malignancies, the enzyme telomerase is essential for sustaining the cancer cells' limitless capacity for replication. The absence of telomerase expression and the lack of an immortal phenotype in normal adult tissues suggest that telomerase is a prospective therapeutic target for the treatment of a variety of tumor forms. At every cell division, telomeres will shrink if telomerase is not active. Apoptosis, cell senescence, and chromosomal instability are initiated when the telomeres become critically short. Telomeres are stabilized in the majority of rapidly expanding cancers by reactivating telomerase. In numerous tumor forms, it has been demonstrated that telomerase inhibition inhibits the development of cancer cells. Telomerase inhibitors have been discovered over the past 10 years as a result of substantial basic research into the mechanisms regulating telomeres, which may offer a potent, nearly universal cancer treatment approach. A short-chain oligonucleotide called imetelstat [GRN163L, Geron Corporation] has a high affinity and specificity for the RNA component of telomerase's template region [hTR or hTERC]. Researchers conduct an examination of articles that are in accordance with the issue to be studied. Articles used in literature review are obtained through the database of international journal providers through PubMed, we investigated clinical studies and discussed what happened in these clinical studies and the extent of the effectiveness of imetelstat in treatment of cancer. Articles proved that imetelstat could enhance cancer treatment. Articles proved that Imetelstat is promising therapeutic agents for cancer treatment. In this review, we suggest that formulating and following treatment, Further studies are needed to determine the related mechanisms to enhance Imetelstat efficacy.